LITERATURE REVIEW THE INFLUENCE OF COMPENSATION AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT PT SUMMARECON AGUNG TBK - Febriyanti, Berliana Samuji (Jurnal Akuntansi, Manajemen dan Ekonomi, 2024)
Previous research/relevant research is very important on research issues or scientific articles. Previous research/relevant research is a function to support the theory and phenomena of the relationship or influence between variables. This article reviews the factors that influence employee performance, namely: compensation, and work discipline, a study of the Business Research Methodology literature. Writing this article aims to build a hypothesis of the influence between variables to be used in further research. The results of this literature review article are: 1) Compensation has an effect on Employee Performance; and 2) Work Discipline affects Employee Performance.